PRONUNCIATION ERRORS MADE BY EFL STUDENT TEACHERS IN SPEECH PERFORMANCE - Diah Dwi Lestari; Fitri Budi Suryani; Nuraeningsih Nuraeningsih (Universitas Muria Kudus, 2020)
Pronunciation is one of the key factors in communication. The different pronunciation or different sounds will cause different meanings. It is known that the sound of English vowels and consonants are so much different from Indonesian vowels and consonants. A slip of pronunciation might occur and cause listeners misunderstand the message.This study is aimed at finding the pronunciation errors and the factors contributing to the pronunciation errors made by the EFL student teachers in speech performance.A descriptive qualitative research design was used. The data were collected through document analysis and interview. The result of the study shows that there were 79 errors found, meanwhile the factors contributing to the students’ pronunciations consists of internal and external factors.